1995
DOI: 10.1128/jcm.33.4.791-793.1995
|View full text |Cite
|
Sign up to set email alerts
|

Detection of vancomycin resistance in enterococci by the Alamar MIC system

Abstract: The ability of the Alamar microdilution MIC system to detect vancomycin resistance in enterococci was evaluated by comparing the results with an agar dilution screen method. Of 100 strains tested, 41 were resistant and 47 were susceptible by both tests. Five strains were intermediate and one was resistant by the Alamar MIC system but susceptible by the agar screen. Three strains each were susceptible or intermediate by the Alamar MIC system but resistant by the agar screen. The predictive values for the Alamar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 9 publications
0
16
1
Order By: Relevance
“…Several studies have evaluated the abilities of commercial and reference antimicrobial susceptibility testing methods to detect vancomycin resistance in Enterococcus isolates (3,(9)(10)(11)(12)(13)(14)(15)(16). Those studies which have evaluated current versions of automated or semiautomated commercial systems, such as the Vitek system (bioMerieux, Inc.), the MicroScan Rapid system (Baxter Health Care Corp., West Sacramento, Calif.), or the Alamar MIC system (Alamar Biosciences, Sacramento, Calif.), have shown that these methods do not reliably detect vancomycin resistance in enterococci (11,13,15,16). Reasons for the poor performance of these systems likely include the composition of growth media and the relatively short incubation times that are used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have evaluated the abilities of commercial and reference antimicrobial susceptibility testing methods to detect vancomycin resistance in Enterococcus isolates (3,(9)(10)(11)(12)(13)(14)(15)(16). Those studies which have evaluated current versions of automated or semiautomated commercial systems, such as the Vitek system (bioMerieux, Inc.), the MicroScan Rapid system (Baxter Health Care Corp., West Sacramento, Calif.), or the Alamar MIC system (Alamar Biosciences, Sacramento, Calif.), have shown that these methods do not reliably detect vancomycin resistance in enterococci (11,13,15,16). Reasons for the poor performance of these systems likely include the composition of growth media and the relatively short incubation times that are used.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of all of the above studies may be the inconsistent definition for the "gold standard" or reference susceptibility result. Some investigators have compared test results of the study method to a broth dilution result (11,13), while others have compared the results of the study method to results obtained by using either agar dilution (9,14), disk diffusion (15), the Micro Scan Rapid method (15,16), or E-test method (12) or by comparing results to the vancomycin resistance genotype (3,10,11). Furthermore, for two of these studies, evaluations were limited to Enterococcus isolates with high-level vancomycin resistance (3,12).…”
Section: Discussionmentioning
confidence: 99%
“…Vancomycin resistance in enterococci has recently become a clinical problem due to a lack of alternative therapies (4,5,14,19). Three major phenotypes of vancomycin-resistant enterococci have been described (12,28). These are the vanA strains, which show high-level vancomycin resistance (MICs of Ͼ32 g/ml) and resistance to teicoplanin; vanB strains, which have variable resistance to vancomycin (MICs of 4 to Ն128 g/ml) and susceptibility to teicoplanin; and vanC motile strains, which show intrinsic resistance to low levels of vancomycin (MICs of 2 to 32 g/ml) and susceptibility to teicoplanin.…”
Section: Discussionmentioning
confidence: 99%
“…Automated systems, including the Vitek and MicroScan systems, have been developed to identify and to determine the antimicrobial susceptibility of enterococci (1,2,18,22,23,(25)(26)(27)(28). Previous studies have shown conventional MicroScan panels to be reliable in the identification of Enterococcus spe-cies, even though the data bank includes only E. faecalis, E. faecium, E. durans, and E. avium (24).…”
mentioning
confidence: 99%
“…The system can be used for susceptibility testing of gram-positive and gram-negative bacteria and for yeasts. It has been evaluated for gram-negative bacteria by Baker et al (3), for yeasts by Pfaller and colleagues (14,15), and for enterococci (vancomycin only) by Tenover et al (18) and Zabransky et al (22). The evaluations for gram-negative bacteria and yeasts indicated that the Alamar method is a satisfactory alternative to conventional MIC methods (3,14,15).…”
mentioning
confidence: 99%